CHARACTERIZATION OF TABAH BLACK RICE TYPE CULTIVATED IN TIDAL RICE FIELD - Purba, Yohanda Samuel; Syafiuddin, Wasi'an; Palupi, Tantri (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACT Characterization was very essential to identify the description of the black rice type characters. This study aims to determine the morphological and agronomic characteristics of Tabah black rice qualitatively and quantitatively, based on the Guidance of Rice Characterization and Evaluation System (Ministry of Agriculture, 2003). The research was carried out in tidal rice at the Sungai Kakap Seed Center Developer. Observations were made measure the qualitative and quantitative black rice phenotypes. The results showed that the agronomic character of Tabah black rice had the ability to medium breed (14 tillers), plant height in the maximum vegetative phase 119,08 cm classified as medium, panicle and overall neck panicle emergence, grain fertility 84,48% classified as fertile and plant age 151 days, and were classified as deep length. Morphological characters were seed height 37,48 cm, leaf length 58,72 cm classified as medium, leaf width 1,72 cm classified as wide, surface of rough hairy leaves, 37,6o leaf angle classified as upright, flag leaf angle 44,8o classified as medium, light green leaf neck, white leaf ears colorless, golden yellow leaf segment, light green leaves (Yellow-Green Group 146 B), green leaf midrib, ligula is 1,8 cm classified as long, ligula is white (Yellow-Green Group 145 A), ligula shape is 2-cleft, the stem angle was 33,7o classified as medium, the stem was yellow gold (Yellow-Green Group 151 D), the panicle was 27,43 cm, panicle type was between medium and open, drooped panicle, seed length 9,87 mm was classified as very long, seed width was 2,72 mm, seed thickness was 2,05 mm and weight of 100 grains was 2,17 grams with 13,6% moisture content. Keywords : agronomy, black rice, characterization, morphology, Tabah rice